Machinery production networks in Latin America: A quantity and quality analysis - Mateus Silva Chang (Latin American Economic Review, 2017)
This paper investigates the effects that the increase in the importation of machinery parts and components and the changes in the supplier composition had in the trade of final products and parts and components inside Latin America. In our analysis, we consider these effects according to two dimensions: a quantity one that captures whether there was an intensification of trade and a quality one that captures changes in the sophistication of the traded goods. The research employs disaggregated trade data obtained from UN Comtrade for 17 Latin American countries between 1996 and 2011. We find evidence that an increase in the importation of parts and components from Latin America had positive impacts on both the quantity and quality dimensions. Subregional heterogeneities revealed that, in general, imports from East Asia had positive effects on the quantity dimension, nurturing the expansion of machinery production networks inside Latin America, and on the quality dimension, increasing the sophistication of the products traded inside Latin America, especially for Mercosur member exports. Imports from North America had positive quantity effects, especially for exports of countries from the Andean Community, Central America, Chile, and Mexico.
Keywords: F14; F15; F23; 330; Machinery trade; Fragmentation; International production networks; Latin America